SISTEM INFORMASI GEOGRAFIS PEMETAAN PETERNAKAN AYAM NEGERI/RAS DI KABUPATEN BATANG BERBASIS WEB - Afthon Arif Afthon (CV. ALIM'SPUBLISHING, 2024)
This research aims to analyze the strategy for developing laying chicken businesses in Batang Regency. This is because the current obstacles faced by chicken farming entrepreneurs will have an impact on business continuity, so a strategy design that is right on target is needed. Therefore, further analysis is needed on the business processes carried out in order to be able to compete with competitors competitively. This research is a qualitative descriptive study. Data was taken through direct observation, interviews and taking documents from chicken breeders in Batang Regency. The method used in this research is a purposive sample, namely taking samples with a specific purpose. This research uses primary data. The validity of the data in this research uses triangulation techniques. Data analysis in this research is qualitative with a descriptive analysis and interpretation approach. The results of the analysis prove that chicken breeders are in quadrant 1 position or support aggressive strategies to be able to develop and survive amidst increasingly competitive competition.